IMPROVING STUDENTS’ ABILITY IN READING NARRATIVE TEXT BY USING THINK PAIR SHARE STRATEGY IN EIGHTH GRADE OF SMP IT AR-RASYID MEDAN SENEMBAH, TANJUNG MORAWA - Utami Dewi (UIN Sumatera Utara, 2016)
The aim of study was to find out improvement of students’ ability in reading narrative text by using TPS strategy. This study was conducted by applying Classroom Action Research (CAR), which was carried out through four steps. They were plan, action, observation and reflection The subject of research was the grade VIII-A students of SMP IT AR-Rasyid Medan Senembah, TanjungMorawa which consisted of 30 students academic years 2015/2016. The research was conducted in two cycle, cycle I consisted of three meetings and cycle II consisted of two meetings. Instruments for data collection were test, observation sheet, interview sheet, diary note and documentation.Based on the result of the data analysis showed that mean of the first cycle was 63,3. The mean of second cycle was 73,5. The percentage of students who got point up 70 also grew up. In the pre test, students who got up 70 were only 1 of 30 students (3,3 %). In the post test of cycle I, students who got up 70 were only 14 of 30 students (46,6 %). It mean that there was improvement about 43,3 %. In the post test of cycle II, students who got up 70 were 26 of 30 students (86,7 %). The improvement was about 40 %. The total improvement of the students’ score from the pre test to post test of cycle II 83,3%. So the result of the research showed that Think Pair Share (TPS) strategy significantly improved students’ ability in reading narrative text.Key Word: Improving Ability, reading, narrative teks, Think Pair Share Strategy, Class Room